Building a Patriotic Millennial Generation Through the Festive Independence Competition Activities in Panggungrejo Subdistrict - Risa, Dea Apullan Lia; Laili, Innayatul; Mutimah, Nihayatul; Fadhilah, Puspita Ajeng (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study aims to cultivate patriotism among Panggungrejo Subdistrict's millennials through technology-enabled community activities. Utilize a participatory approach, the research explores the effectiveness of organized events in fostering national pride among youths. Method: The study involves coordination between the youth organization and KKN-T Uniwara students, focusing on planning, socialization, implementation, and evaluation stages. Data collection includes meetings, task distribution, and participant engagement in competitions, with analysis emphasizing cooperation patterns. Practical Applications: The research offers insights into community development and youth engagement efforts. Understanding the impact of organized activities can inform policymakers and community leaders in designing targeted programs to promote national identity, leveraging technology for enhanced communication and participation. Conclusion: This study highlights the role of community initiatives in instilling patriotism, providing practical implications for fostering a sense of national unity among millennials through organized activities.